PENGARUH RASIO KREDIT, RASIO LIKUIDITAS, DAN TOTAL ASET TERHADAP LABA BANK KONVENSIONAL DAN BANK SYARIAH DI INDONESIA - Rifda Nabila; Nazaruddin Malik; Syamsul Hadi (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study is to analyze the effect of credit ratios (NPL/NPF), liquidity ratios (LDR/FDR), and total assets on profits of conventional banks and Islamic banks during 2010-2017. This type of research uses quantitative research, which uses the annual report data of each bank that has been published by the official website of each bank. Then analyzed using panel data regression analysis twice which was processed using Eviews 9. The results of the first regression for conventional banks show that NPL has a significant negative effect on profits with a coefficient -0.051850, LDR has a significant positive effect on profits with a coefficient 0.009284, total assets have a significant positive effect on profits with a coefficient 0.477739. The second regression result, for Islamic banks, shows that NPF has a significant negative effect on profit of Islamic banks with a coefficient -0.141129, FDR has a positive insignificant effect on Islamic bank profits with a coefficient 0.015131, total assets have a significant positive effect on Islamic bank profits with a coefficient 0.331709.